10.0k views
5 votes
F(x) = x^2 - 3x+ 5 g(x) = 2x^2 - 4x - 11 what is h(x) = f(x) + g(x)

2 Answers

4 votes

Answer:


\huge\boxed{(f+g)(x)=3x^2-7x-6}

Explanation:


f(x)=x^2-3x+5\\\\g(x)=2x^2-4x-11\\\\(f+g)(x)=f(x)+g(x)\\\\\text{substitute}\\\\(f+g)(x)=(x^2-3x+5)+(2x^2-4x-11)\\\\(f+g)(x)=x^2-3x+5+2x^2-4x-11\\\\\text{combine like terms}\\\\(f+g)(x)=(x^2+2x^2)+(-3x-4x)+(5-11)\\\\(f+g)(x)=3x^2-7x-6

User DelphiNewbie
by
5.3k points
6 votes

Hey there! :)

Answer:

h(x) = 3x² - 7x - 6

Explanation:

Calculate h(x) by adding the two polynomials:

h(x) = f(x) + g(x):

h(x) = x² - 3x + 5 + 2x² - 4x - 11

Combine like terms:

h(x) = 3x² - 7x - 6

User Jasonmerino
by
5.7k points